2014
DOI: 10.1016/j.arthro.2014.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Tear Degeneration and Cell Apoptosis in Smokers Versus Nonsmokers

Abstract: Purpose-The purpose of this study was to assess the effect of smoking on supraspinatus tendon degeneration, including cellular alterations, proliferation, and apoptosis of tendon cells.Methods-Supraspinatus tendon samples of 10 smokers and 15 nonsmokers with full-thickness tears were compared, focusing on the severity of tendon histopathology including apoptosis (programmed cell death), cellularity, and proliferation. Immunohistochemistry was used to assess the density of apoptotic cells and proliferation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 36 publications
2
53
3
1
Order By: Relevance
“…Similarly, histologic analysis also revealed no significant differences in cellularity, cell shape, or collagen fiber alignment. Overall, tendons from both groups demonstrated marked cellularity and rounding of tenocytes, consistent with previous literature . Given that there was no difference in cellularity or cell shape, the equivalent collagen fiber alignment between groups suggests that maturation of the healing tendon is not delayed in the nicotine treated group.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, histologic analysis also revealed no significant differences in cellularity, cell shape, or collagen fiber alignment. Overall, tendons from both groups demonstrated marked cellularity and rounding of tenocytes, consistent with previous literature . Given that there was no difference in cellularity or cell shape, the equivalent collagen fiber alignment between groups suggests that maturation of the healing tendon is not delayed in the nicotine treated group.…”
Section: Discussionsupporting
confidence: 88%
“…This is an area of vascular anastomosis, plagued by microcirculatory disturbances and tissue hypoxia [14]. The oxidative stress due to production of reactive oxygen species and cellular apoptosis could be the cause of the degeneration, tendon ruptures and reduced number of tenocytes in patients who smoke [15].…”
Section: Discussionmentioning
confidence: 99%
“…100 Lundgreen et al found that supraspinatus tendon samples from smokers with full-thickness tears demonstrated increased density of apoptotic cells accompanied by reduced tenocyte density and upregulation of proliferative activity. 101 Given that the establishment of a vascular supply to the rotator cuff tendon is one of the critical factors in effective cuff healing, smoking as a pathologic mechanism for impaired healing is significantly supported.…”
Section: Smokingmentioning
confidence: 99%